Breadwinner’s Propaganda within the English Foreign Movie’s Depiction of Middle-East - Almughni, Opel; Edward, Edward; Fauzi, Mohammad (Universitas Lancang Kuning, 2020)
Film is one of media products whose development as art product that have free-expression, it is also one of the mainstream media. The presence of a film provides its own color in other media mass competition to benefit for many people. This study deals with an analysis of propaganda by film techniques used in The Breadwinner film. The purpose of this study is to find out the types, the meanings and the functions of Propaganda used in The Breadwinner film. The data are taken from the script of The Breadwinner, Angelina Jolie as A Producer released on 8th September 2017 and directed by Nora Twomey. The data analysing technique used in this study is descriptive qualitative research with a document or content analysis as the research type. This thesis categorizes and analyses of Propaganda that found in The Breadwinner film. From the analysis, there are 7 types of propaganda by film techniques, this study focused on analysing in Glittering generalities techniques. The findings show that there is some propaganda that used in The breadwinner that had been analysed into functions propaganda especially glittering generalities.